2022
DOI: 10.1161/svin.121.000142
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Acute Transient Contrast‐Induced Neurologic Deficit: A Systematic Review With Meta‐Analysis

Abstract: BACKGROUND After MR CLEAN (Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands) demonstrated that endovascular therapy improved outcomes in patients with stroke, the number of endovascular procedures has risen sharply. We describe acute transient contrast‐induced neurological deficit (ATCIND), a group of neurological syndromes associated with arterial contrast administration during angiography. Our goal is to elucidate the incidence, risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…It has been suggested that higher doses and lower temperatures of contrast media, kidney disorders, arterial hypertension, and acute cerebral infarction are risk factors for CIE [ 9 ]. Higher contrast dose and prior stroke were corroborated as risk factors in a recent meta-analysis [ 10 ]. However, lower doses of contrast agent have also been associated with CIE [ 11 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It has been suggested that higher doses and lower temperatures of contrast media, kidney disorders, arterial hypertension, and acute cerebral infarction are risk factors for CIE [ 9 ]. Higher contrast dose and prior stroke were corroborated as risk factors in a recent meta-analysis [ 10 ]. However, lower doses of contrast agent have also been associated with CIE [ 11 ].…”
Section: Discussionmentioning
confidence: 88%
“…It has been suggested that higher doses and lower temperatures of contrast media, kidney disorders, arterial hypertension, and acute cerebral infarction are risk factors for CIE. 9 Higher contrast dose and prior stroke were corroborated as risk factors in a recent meta-analysis. 10 However, lower doses of contrast agent have also been associated with CIE. 11 The doses reported in the literature varied widely depending on procedure type with volumes as low as 24 mL in a cerebral angiography case 6 and as high as 360 mL in a spinal angiography case. 12 Our patient received a total volume of contrast of 125 mL.…”
Section: Pathophysiology and Risk Factorsmentioning
confidence: 99%
“…It was first described in 1970 as contrast-induced neurologic injury secondary to coronary angiography. 1 More recently, these clinical syndromes have been associated with the administration of localized contrast medium injections through coronary, carotid, and cerebral angiography. 1 - 7 In a recent systematic review, the incidence of this rare entity after PCI was estimated to be 0.15%, even less common than the incidences reported in prior contrast studies.…”
Section: Discussionmentioning
confidence: 99%
“… 1 More recently, these clinical syndromes have been associated with the administration of localized contrast medium injections through coronary, carotid, and cerebral angiography. 1 - 7 In a recent systematic review, the incidence of this rare entity after PCI was estimated to be 0.15%, even less common than the incidences reported in prior contrast studies. 1 Risk factors for the development of ATCIND include kidney dysfunction, large contrast dose, and contrast agents that have higher osmolality and lower hydrophilicity, 1 which are characteristics of the contrast agents used in PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the risk factors that have been associated with CIE, one meta-analysis showed that higher contrast doses (OR, 1.072; CI, 0.952-1.192), and having a history of stroke (OR, 5.153; CI, 1.726-8.581), were significant risk factors for developing CIE. Other significant risk factors were renal dysfunction, anticoagulant use, heart failure, Ioversol (as compared with iopromide), and isolated posterior circulation cerebral angiography. They have also found that visual manifestations were more common in patients that were given a contrast dose of more than 150 mL (OR, 7.083; CI, 1.172-42.793) [ 14 ]. However, one case showed manifestations after the administration of only 25 ml of iopromide with symptoms developing immediately within the procedure [ 15 ].…”
Section: Discussionmentioning
confidence: 99%